A Study on Technical Analysis of Equity Shares of Tata Motors for the Period from November 2008 to April 2009 - Venkatalakshmi, M.; Sindhu, C. M. (Indian Journal of Finance, 2010)
A stock market is a public market for the trading of a company's stocks and derivatives at an agreed price; these are securities listed on a stock exchange as well as those only traded privately. Tata Motors, the first company from India's engineering sector to be listed in the New York stock exchange, (September 2004) has also emerged as an international automobile company. The study is concerned with the technical analysis of equity shares of Tata Motors for the period from November 2008 to April 2009 with a view to analyze and understand the equity shares of the Tata Motors. The study is fully based on the secondary data which have been collected from the company reports and websites.